2016
DOI: 10.3184/174751916x14743924874916
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Amidrazones with 2,3-Diphenylcyclopropenone: Synthesis of 3-(aryl)-2,5,6-Triphenylpyrimidin-4(3H)-ones

Abstract: Amidrazones react with 2,3-diphenylcyclopropenone to give 3-aryl-2,5,6-triphenylpyrimidin-4(3H)-one derivatives in good yields. The synthesised compounds were characterised by spectroscopic tools and their structures confirmed by X-ray crystallography. A rational mechanism of formation of the products is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…111 Aly et al in 2016, successfully synthesized pyrimidines 117af in 67-87% yield, via the reaction between 116a-f and 1b in EtOH and Et 3 N (Scheme 70). 112 The proposed reaction mechanism is illustrated in Scheme 71; the carbonyl group of cyclopropenone was attacked by the hydrazine nitrogen atom yielding intermediate B, following which an amidine-like reaction of N-3 to carbonyl may occur to obtain salt C. Nucleophilic addition to positively charged Mohan and Jose, in 2017, have reported that reaction between (E)-disubstituted diazene-1,2-dicarboxylates 120a-j and diarylcyclopropenone 1 in DCM at room temperature. The reaction was catalyzed by PPh 3 to afford substituted 1,3-oxazin-6-one 121a-j in 50-70% yield (Scheme 73).…”
Section: Tert-butoxidementioning
confidence: 99%
See 2 more Smart Citations
“…111 Aly et al in 2016, successfully synthesized pyrimidines 117af in 67-87% yield, via the reaction between 116a-f and 1b in EtOH and Et 3 N (Scheme 70). 112 The proposed reaction mechanism is illustrated in Scheme 71; the carbonyl group of cyclopropenone was attacked by the hydrazine nitrogen atom yielding intermediate B, following which an amidine-like reaction of N-3 to carbonyl may occur to obtain salt C. Nucleophilic addition to positively charged Mohan and Jose, in 2017, have reported that reaction between (E)-disubstituted diazene-1,2-dicarboxylates 120a-j and diarylcyclopropenone 1 in DCM at room temperature. The reaction was catalyzed by PPh 3 to afford substituted 1,3-oxazin-6-one 121a-j in 50-70% yield (Scheme 73).…”
Section: Tert-butoxidementioning
confidence: 99%
“…Aly et al in 2016, successfully synthesized pyrimidines 117a–f in 67–87% yield, via the reaction between 116a–f and 1b in EtOH and Et 3 N (Scheme 70). 112…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…25 The reaction of alkenylidenehydrazine-carbothioamides with cyclopropenone, as well as the presence of nucleophilic sites like azomethine carbon and sulfur atoms, resulted in 3,5-disubstituted 1,3,4-thiadiazolyl-2,3-diphenylpropenones. 26 The reaction of cyclopropenone with various aldehyde 4-phenyl thiosemicarbazones in acetic acid afforded pyrrolo[2,1- b ]oxadiazoles through [2 + 3]cycloaddition; H 2 S was eliminated. 27 Moreover, 2,4-disubstituted thiosemicarbazides reacted with cyclopropenone to afford the corresponding pyridazines.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, we have reported that amidrazones reacted with 2,3-diphenylcyclopropenone via extrusion of ammonia to give 3-(aryl)-2,5,6-triphenylpyrimidin-4(3H)-ones. 6 For a very long time, the usefulness and great therapeutic value of the pyrazole nucleus have been recognized and the activities of this nucleus have been evaluated. 7 Phenazone (antipyrine), a pyrazolin-5-one, was one of the first synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%